Leadership Styles and Employee Well Being: A Systematic Review of Global Organizational Behavior Studies - Tobari, Tobari (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This research explores the influence of a hybrid leadership style on employee well-being in a remote work context. The systematic literature review method following PRISMA guidelines was applied to analyze 25 relevant studies. The analysis results show that the integration of elements of transactional and transformational leadership in a hybrid leadership style can significantly improve employee welfare. These findings emphasize the importance of the role of leadership in creating a supportive work environment, especially in the digital era that prioritizes virtual interactions. Additionally, this research identifies gaps in the existing literature, including limitations in cultural contexts and industrial sectors. The practical and theoretical implications of the results of this research provide insight for organizational leaders and human resource management practitioners in formulating adaptive and responsive leadership strategies. Further research is recommended to investigate other variables that may influence the relationship between hybrid leadership and employee well-being.